Development of a Science e-Book by Exploring Traditional Food Within a PBL-ESD Framework to Foster Students’ Problem-Solving Skills - Pratiwi, Reni Indah Ayu; Widowati, Asri (Jurnal Pendidikan MIPA, 2024)
This study aims to determine the effect of science e-books, with a focus on the topic of mixture separation, delivered through the Problem-Based Learning (PBL) model integrated with the local potential of Petis as a traditional food, to improve students' problem-solving skills. The research was conducted at SMPN Yogyakarta in the second semester of the 2023/2024 academic year, involving 24 students in class VIII as a randomly selected research sample. The research was a quasi-experiment with a non-equivalent control group design. The instrument used was a problem-solving skills test consisting of 10 questions. The paired t-test results show a significance level of 0.001 which is smaller than the value of α = 0.05 so it can be concluded that there is a significant difference between the pretest and posttest results of students' problem-solving skills. The N-gain of the pretest posttest of problem-solving skills is 0.46 with the acquisition per indicator as follows: understanding the problem (0.8), analyzing the problem (0.7), planning the solution (0.6), implementing the solution (0.6), and evaluating (0.5).  The effect size analysis shows a value of 0.94 which is included in the large category. Thus, this study shows that the science e-Book by exploring traditional food within a PBL-ESD has a substantial positive influence on students' problem-solving skills.      Keywords: e-Book, PBL-ESD, problem solving skills, traditional food.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1604-1617